2003
DOI: 10.1007/s00122-003-1226-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a DRE-binding transcription factor from a halophyte Atriplex hortensis

Abstract: Environmental stresses, such as salinity, drought and cold, can induce the expression of a large amount of genes. Among these are many transcription factors that regulate the expression of downstream genes by specifically binding to cis-elements or forming transcriptional complexes with other proteins. In the present study, a DREB-like transcription factor gene, named AhDREB1, was isolated from a halophyte Atriplex hortensis. AhDREB1 encoded a protein containing a conserved EREBP/AP2 domain featuring the DREB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…Likewise, the constitutively overexpressing CBF3/DREB1A and ABF3 transgenic rice showed better drought and salinity tolerance without any growth inhibition or phenotypic anomalies . The overexpression of AhDREB1 accumulated putative downstream target genes and also conferred improved survival rate to transgenic tobacco plants under salt stress as compared to the wild-type plants (Shen et al, 2003b). The over-expression of OsDREB1F greatly enhanced tolerance of plants to high salinity, drought, and lowtemperature both in rice and Arabidopsis, thus playing a significant role in plant stress signal transduction .…”
Section: The Cbf/dreb Regulonmentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise, the constitutively overexpressing CBF3/DREB1A and ABF3 transgenic rice showed better drought and salinity tolerance without any growth inhibition or phenotypic anomalies . The overexpression of AhDREB1 accumulated putative downstream target genes and also conferred improved survival rate to transgenic tobacco plants under salt stress as compared to the wild-type plants (Shen et al, 2003b). The over-expression of OsDREB1F greatly enhanced tolerance of plants to high salinity, drought, and lowtemperature both in rice and Arabidopsis, thus playing a significant role in plant stress signal transduction .…”
Section: The Cbf/dreb Regulonmentioning
confidence: 96%
“…The activation of these transcripts is organ-specific and comparative to the extent of the stress given. When exposed to salt stress, AhDREB1 was highly expressed in roots but less significantly in stems and leaves (Shen et al, 2003b). It was observed that OsDREB1F was constitutively expressed throughout the plant with highest expression in panicles and callus than in the other tissues .…”
Section: The Cbf/dreb Regulonmentioning
confidence: 98%
“…This is reasonable, since roots usually sense stress signals first, due to contact with the soil; plants need to express defense-related genes in their roots in time to promote survival under severe conditions (Li et al, 2005). Shen et al (2003) found that AhDREB1, a DREB-type gene from Arabidopsis hortensis, was induced in roots, but not in stems or leaves.…”
Section: Gm18srrna Gmdreb1amentioning
confidence: 99%
“…The orthologous genes of CBF have been found in most crop plants examined so far, including canola (B. napus), soybean (Glycine max), broccoli (Brassica oleracea), tomato, alfalfa (Medicago sativa), tobacco (Nicotiana tabacum), cherry (Prunus avium), strawberry (Fragaria spp. ), wheat, rye (Secale cereale), corn (Zea mays), rice, and barley (Jaglo et al, 2001;Choi et al, 2002;Gao et al, 2002;Owens et al, 2002;Dubouzet et al, 2003;Francia et al, 2004;Shen et al, 2003aShen et al, , 2003bVagujfalvi et al, 2003;Xue, 2003). Many of the putative orthologs have been functionally tested, indicating conservation of the pathway in those plant species.…”
Section: Engineering Cold and Drought Tolerance In Crop Plants Based mentioning
confidence: 99%